1980
DOI: 10.1007/bf01011933
|View full text |Cite
|
Sign up to set email alerts
|

Lectin binding by microvillous membranes and coated-pit regions of human syncytial trophoblast

Abstract: The distribution of saccharides on the microvillous membrane of the human syncytial trophoblast was investigated using ferritin conjugates of four lectins: concanavalin A (specific for alpha-D-manno- and alpha-D-glucopyranosyl residues), wheatgerm agglutinin (specific for N-acetylglucosamine), Limulus polyphemus lectin (specific for N-acetylneuraminic acid), and Lotus tetragonolobus lectin (specific for alpha-L-fucose). Concanavalin A and wheatgerm agglutinin (WGA) reacted strongly with the surface membrane an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…It has been pointed out that the brush border of the syncytiotrophoblast is heavily glycosylated as the primary site for feto-maternal interactions (Whyte 1980;Sgambati et al, 2002). In this study, we demonstrated that the brush border of the syncytiotrophoblast layer strongly expressed GlcNAc, and weakly expressed sialic acid.…”
Section: Effect Of Other Conditionssupporting
confidence: 56%
See 2 more Smart Citations
“…It has been pointed out that the brush border of the syncytiotrophoblast is heavily glycosylated as the primary site for feto-maternal interactions (Whyte 1980;Sgambati et al, 2002). In this study, we demonstrated that the brush border of the syncytiotrophoblast layer strongly expressed GlcNAc, and weakly expressed sialic acid.…”
Section: Effect Of Other Conditionssupporting
confidence: 56%
“…For example, the transferrin receptor and alkaline phosphatase in the brush border are known to be associated with N-linked oligosaccharides and 2,3-linked sialic acid (Fukushima et al, 2003). Alkaline phosphatase is also reported to bind to Con A, and clathrin-coated pits were implied to react with WGA (Whyte, 1980). Although the glycosylation of most of these molecules in the brush border has yet to be fully elucidated, our finding that the trophoblastic brush border mainly expressed GlcNAc accords with previous reports (Reitsma et al, 2007).…”
Section: Effect Of Other Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lectins labeled with fluorescein isothiocyanate (FITC) or horseradish peroxidase have been extensively used as histochemical reagents in the study of both normal [3,9,10,12,14,15,18,191 and pathologically altered [l, 2, 4, 5, 13, 161 human and animal tissues. Labeled lectins have been used to characterize human placental tissue, but the data are fragmentary [6,7,11,20,211 and often inconsistent or contradictory, so that a complete histochemical map of lectin-binding carbohydrate sites is still lacking. These discrepancies are due, in part, to the different protocols used in different studies [17] and, in part, to the lack, until recently, of commercially available purified-lectin preparations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because of the presence of proteoglycans in placental fibrinoid [Kisalus and Herr, 1988], the reaction of three lectins within placental fibri noid was investigated: Ulex europaeus (UEA-I), which is known to stain placental endothelium and circulating blood cells [Lang et al, 1993], Bandeiraea simplicifolia lectin (BS-I), which labels cell types with a predominantly secre tory activity [Murakami et al, 1992]. Lycopersicon escttiention (LEA) binds to the N-acetyl-D-glucosamine [Nachbar et al, 1980] associated with the syncytiotrophoblast [Whyte. 1980],…”
Section: Introductionmentioning
confidence: 99%